Vitamin D Receptor (VDR) Gene Polymorphism in Kurdish Patients Diagnosed with Different Stages of Colorectal Cancer - Ahmad, Narmeen Salih (Journal of Sulaimani Medical College, 2025)
Background: Vitamin D, which mainly contributes to calcium metabolism and bone diseases, mediates its biological functions through binding to the vitamin D receptor (VDR). VDR acts as a transcription factor to modulate several gene expressions. Single-nucleotide polymorphisms (SNPs) in the VDR gene have been associated with CRC in different ethnic groups. Objectives: The objective of this study was to investigate the association of four common SNPs in the VDR gene (FokI, BsmI, ApaI, and TaqI) with the risk of CRC in a Kurdish population. Methods: In this study, 100 CRC patients and 50 healthy individuals matched in age and gender were recruited. Genomic DNA samples were extracted from the peripheral blood cells, and VDR gene SNPs (FokI, BsmI, ApaI, and TaqI) were identified using amplification refractory mutation system-polymerase chain reaction (ARMS-PCR). Results: None of the four common SNPs in the VDR gene individually had any significant effect on CRC risk. The evaluation of haplotypes for FokI, ApaI, and TaqI SNPs revealed that FAT (haplotype)(OR= 3.322, 95% CI (1.747 - 6.317), p<0.05) might enhance CRC risk, while faT haplotype (OR= 0.34, 95% CI (0.16 - 0.73), p<0.05), fAT haplotype (OR=0.25, 95% CI (0.11 - 0.58) and FaT haplotype (OR= 0.20, 95% CI (0.08 - 0.51), p< 0.05) are protective against CRC development. Conclusion: This study found that the investigated individual SNPs neither increased nor decreased the risk of CRC in the selected Kurdish population. This finding needs to be confirmed in a large sample size in different cancer centers to understand the potential roles of the selected polymorphisms in CRC development
Keywords: Colorectal cancer; Vitamin D; Vitamin D receptor; Single nucleotide; FokI